PENGARUH KUALITAS PELAYANAN, KESADARAN WAJIB PAJAK, DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA UMKM YANG TERDAFTAR DI KPP PRATAMA SEMARANG SELATAN) - Riadita, Farah Alifa; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
The current government continues to increase efforts to explore domestic revenues from the tax sector because the tax sector is a very potential revenue to be explored, where the results of domestic tax revenues are a source of government funding to improve welfare and prosperity and to overcome social problems. Seeing this requires a substantial tax receipt for funding in carrying out state responsibilities. The greater the tax revenue received, the greater the income earned by a country. The purpose of this study is to determine the effect of service quality, taxpayer consciousness, and tax knowledge on taxpayer compliance. The hypothesis in this research is the existence influence between the variable of service quality, taxpayer consciousness, and tax knowledge on taxpayer compliance. The results showed that the variable of service quality has a positive and significant effect on taxpayer compliance, the variable of taxpayer consciousness has a positive and significant effect on taxpayer compliance, the variable of tax knowledge has a positive and significant effect on taxpayer compliance. Service quality, taxpayer consciousness, and tax knowledge have positive and significant effect on taxpayer compliance. Taxpayer compliance still needs to be improved so that in this research suggest to socialize the importance of the tax. This research is also expected as an input for the next researcher.